Women with disabilities and the right to work in Nigeria: recommendations for an inclusive public service and labour market - Andrew-Uponi, Omuwa (Department of Public Law, 2025)
In Nigeria, as a result of attitudinal, mobility-related, technological, and physical barriers, the employment rates among persons with disabilities are lower than that of the Nigerian general population, women with disabilities constitute a vulnerable part of the disability population in Nigeria and are more impacted by these barriers. Due to the intersection between gender and disabilities, women with disabilities are often victims of double discrimination and encounter a greater degree of stigmatization in accessing open employment than men with disabilities. Although Nigeria ratified major international and regional disability instruments that guarantee equality and non-discrimination to women with disabilities in the context of employment access, little has been achieved for them in that regard. Furthermore, Nigeria's federal disability law positively addresses disability discrimination and reserves specified quota in public sector employment for persons with disabilities, but patriarchy and gender stereotypes rendered implementation of the quotas for women with disabilities difficult to achieve. This research thesis examines the discrimination experienced by women with disabilities in realizing employment participation and focuses on ways to improve their public and open labour market participation in Nigeria. To this end, the thesis recommends hybrid legislation, best practices, and strategic implementation measures to increase access for women with disabilities in Nigeria's employment sector.